Translation as a tool in linguistic analysis - Zlateva, Palma (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
The English conjunction ‘if’ and its functional equivalents in Russian and in Bulgarian, which normally introduce conditional clauses, have a variety of other functions which may or may not be connected with their invariant meanings. The use of ‘if’ in combination with the negative particle ‘not’ and with the comparative connective ‘as’ to introduce syntactic elements other than conditional clauses is characterised with a whole spectrum of func¬tional meanings, such as concession, gradation, implied suggestion, etc. These meanings and nuances of meaning, which sometimes pose real pro¬blems for the linguist, come to the surface in translations from and into English, Bulgarian and Russian. Interpretations and inter-language trans¬formations involved in the process of translation play the role of semantic analysis and reveal functional peculiarities which are often overlooked in mono-lingual or even in contrastive grammars.